Hippocampal and cortical G protein (Gs alpha, G(o) alpha and Gi2 alpha) mRNA expression after electroconvulsive shock or lithium carbonate treatment. - McGowan, S; Eastwood, S; Mead, A; Burnet, P; Smith, C; Flanigan, T; Harrison, P (1996)
GTP-binding proteins (G proteins) are heteromers composed of alpha, beta and gamma subunits. The expression of some G protein subunits is altered both by affective disorders and by antidepressant treatments. Here we have studied three G protein alpha subunit mRNAs in the hippocampus and frontoparietal cortex of rats treated with lithium for 14 days or with repeated electroconvulsive shock (five shocks over 10 days). After electroconvulsive shock, the three mRNAs changed differentially in the hippocampus. Specifically, Gs alpha mRNA was decreased in CA3 and CA1, whilst G(o) alpha mRNA was increased in dentate gyrus and Gi2 alpha mRNA was reduced in dentate gyrus and CA3. Lithium carbonate treatment produced a modest, uniform increase in the three mRNAs in dentate gyrus and CA3, and a selective elevation of G(o) alpha mRNA in CA1. Neither treatment altered the G protein mRNAs in the cortex nor cyclophilin mRNA in any region. These data extend the evidence that altered G protein expression is a part of the biochemical response to antidepressant treatments. Differences in the molecular and anatomical pattern of the alterations induced by electroconvulsive shock compared to lithium may contribute to their different therapeutic profiles.